The Growth And Yield of Aluminium Tolerant Maize Varieties With The Addition of Cow Manure - Putri, Yolanda; Syarif, Auzar; Putri, Nurwanita Ekasari (Jurnal Agrinika: Jurnal Agroteknologi dan Agribisnis, 2026)
Maize (Zea mays L.) is a strategic food commodity that supports food security and the national economy. However, corn productivity on suboptimal land is often limited by low soil fertility due to acidity and aluminum (Al) toxicity. This study aimed to identify aluminum-tolerant corn varieties under AlCl₃ stress conditions and evaluate their growth and yield on suboptimal land with the addition of cow manure. The study was conducted in two stages. The first stage involved selecting aluminum-tolerant corn varieties using a nutrient culture with a factorial Completely Randomized Design (CRD), involving six corn varieties and two AlCl₃ concentrations (0 ppm and 180 ppm). The results of the first stage indicated that the P32, Bisi 18, and Lamuru varieties were classified as aluminum-tolerant, while the Sukmaraga variety was classified as sensitive but described as adaptable to acidic soils. The second stage was a field trial using a factorial Randomized Block Design (RBD) with four selected corn varieties and three doses of cow manure. The data obtained were tested for F at a significance level of 5% if the Fhit value > F table and continued with Duncan's Multiple Range Test (DMRT). The results showed that two corn varieties (P32 and Bisi 18) provided the best growth, and the results were seen from the length of the cob, the number of cobs, the weight of peeled cobs, and the potential yield per hectare.